1993
DOI: 10.1002/actp.1993.010440602
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of oligothienyl series from X‐ray powder diffraction data

Abstract: The structures of the series of oligothienyls (T4-T5-T6) have been determined and refined from X-ray powder diffraction data using the Rietveld full-profile analysis. Unlike polythiophene, all the molecules in the isomorphous series display no internal symmetry, being only approximately planar within 12". Packing is always achieved through a common molecular disposition, which is usually defined as a herringbone arrangement, with an angle between mean planes of adjacent molecules which spans from 60" to 70".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
108
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 23 publications
20
108
1
Order By: Relevance
“…The "lowtemperature" (LT) structure, [17,18] which is monoclinic, space group P2 1 /n with Z = 4, and the "high-temperature" (HT) structure [19] also monoclinic, but with the space group P2 1 /a and Z = 2. To investigate polymorphism in T6, we have used confocal Raman microscopy in the lattice phonon region to discriminate different crystal lattices.…”
Section: Confocal Raman Mapping Of T6 Bulk Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The "lowtemperature" (LT) structure, [17,18] which is monoclinic, space group P2 1 /n with Z = 4, and the "high-temperature" (HT) structure [19] also monoclinic, but with the space group P2 1 /a and Z = 2. To investigate polymorphism in T6, we have used confocal Raman microscopy in the lattice phonon region to discriminate different crystal lattices.…”
Section: Confocal Raman Mapping Of T6 Bulk Crystalsmentioning
confidence: 99%
“…[3,7,9,16] The two polymorphs in the bulk crystal of T6, previously identified by X-ray diffraction experiments, [17][18][19] have been recently studied by confocal Raman spectroscopy, [20] a versatile and powerful tool for in-situ discrimination of crystal structures. There, we have observed that mixed micro-domains of the two phases may be obtained simultaneously from the same sublimation process and can coexist even in the same crystallite, showing up as physical impurities of one phase inside the other.…”
Section: Introductionmentioning
confidence: 99%
“…Such molecules pack in a herringbone arrangement with at least 2 molecules in a unit cell. [20][21][22][23] Here, the lower Davydov component ͑alias J-band͒ is weakly allowed along the crystal b direction, 20,[24][25][26] leading to b-polarized superradiant 0-0 emission 27 which diminishes with increasing disorder. [28][29][30][31] In helical MOPVn aggregates, coherence affects the PL spectrum in a manner similar to the ideal linear H-aggregates described above.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable structural data currently available have shown that these oligomers are essentially planar with a fully conjugated carbon skeleton. 7,8 Much work has been devoted in past years to -substituted oligothiophenes to obtain soluble materials easy to characterize and process. [9][10][11][12][13][14] In comparison with the -substitution, the R,R′-disubstitution has the advantage of inducing only very small conformational distortions of the outermost rings, thus preserving the conjugation and the electronic properties of the materials.…”
Section: Introductionmentioning
confidence: 99%